1. Neuro-Psychological Benefits of Music Education - Iușcă Dorina Geta (Sciendo, 2022)
The importance of music for the development of society and the individual has been proved over time in a variety of educational and cultural situations. The cortical representations of musical functions (such as melody, harmony, absolute pitch, timbre, rhythm, music memory, and music emotions) offer new perspectives on the implications that musical training has on the development of the brain. Multiple studies have showed that musicians exhibit hyper-development of certain areas of their brains and obtain better results when motor skills, visual tasks and music related processing abilities were tested.